Glia Maturation Factor and Mitochondrial Uncoupling Proteins 2 and 4 Expression in the Temporal Cortex of Alzheimer’s Disease Brain - Thangavel, Ramasamy; Kempuraj, Duraisamy; Zaheer, Smita; Raikwar, Sudhanshu; Ahmed, Mohammad E.; Selvakumar, Govindhasamy Pushpavathi; Iyer, Shankar S.; Zaheer, Asgar (Frontiers in Aging Neuroscience, 2017)
Alzheimer’s disease (AD) is characterized by the presence of neuropathological lesions containing amyloid plaques (APs) and neurofibrillary tangles (NFTs). AD is associated with mitochondrial dysfunctions, neuroinflammation and neurodegeneration in the brain. We have previously demonstrated enhanced expression of the proinflammatory protein glia maturation factor (GMF) in glial cells near APs and NFTs in the AD brains. Parahippocampal gyrus consisting of entorhinal and perirhinal subdivisions of temporal cortex is the first brain region affected during AD pathogenesis. Current paradigm implicates oxidative stress-mediated neuronal damage contributing to the early pathology in AD with mitochondrial membrane potential regulating reactive oxygen species (ROS) production. The inner mitochondrial membrane anion transporters called the uncoupling proteins (UCPs) function as regulators of cellular homeostasis by mitigating oxidative stress. In the present study, we have analyzed the expression of GMF and mitochondrial uncoupling proteins UCP2 and UCP4 in the parahippocampal gyrus of AD and non-AD brains by immunostaining techniques. APs were detected by thioflavin-S fluorescence staining or IHC with 6E10 antibody. Our current results suggest that upregulation of GMF expression is associated with down-regulation of UCP2 as well as UCP4 in the parahippocampal gyrus of AD brains as compared to non-AD brains. Further, GMF expression is associated with up-regulation of inducible nitric oxide synthase (iNOS), the enzyme that induces the production of nitric oxide, as well as nuclear factor kB p65 (NF-κB p65) expression. Also, GMF appeared to localize to the mitochondria in AD brains. Based on our current observations we propose that enhanced expression of GMF down-regulates mitochondrial uncoupling proteins UCP2 and UCP4 thereby exacerbating AD pathophysiology and this effect is potentially mediated by iNOS and NF-κB. Thus, GMF functions as an activator protein that interferes with the cytoprotective mechanisms in AD brains.